Correlating species and spectral diversities using hyperspectral remote sensing in early‐successional fields. Issue 10 (6th April 2017) - Aneece, Itiya P.; Epstein, Howard; Lerdau, Manuel
Abstract: Advances in remote sensing technology can help estimate biodiversity at large spatial extents. To assess whether we could use hyperspectral visible near‐infrared (VNIR) spectra to estimate species diversity, we examined the correlations between species diversity and spectral diversity in early‐successional abandoned agricultural fields in the Ridge and Valley ecoregion of north‐central Virginia at the Blandy Experimental Farm. We established plant community plots and collected vegetation surveys and ground‐level hyperspectral data from 350 to 1, 025 nm wavelengths. We related spectral diversity (standard deviations across spectra) with species diversity (Shannon–Weiner index) and evaluated whether these correlations differed among spectral regions throughout the visible and near‐infrared wavelength regions, and across different spectral transformation techniques. We found positive correlations in the visible regions using band depth data, positive correlations in the near‐infrared region using first derivatives of spectra, and weak to no correlations in the red‐edge region using either of the two spectral transformation techniques. To investigate the role of pigment variability in these correlations, we estimated chlorophyll, carotenoid, and anthocyanin concentrations of five dominant species in the plots using spectral vegetation indices. Although interspecific variability in pigment levels exceeded intraspecific variability, chlorophyll was more varied within species than carotenoids and anthocyanins, contributing to the lack of correlation between species diversity and spectral diversity in the red‐edge region. Interspecific differences in pigment levels, however, made it possible to differentiate these species remotely, contributing to the species‐spectral diversity correlations. VNIR spectra can be used to estimate species diversity, but the relationships depend on the spectral region examined and the spectral transformation technique used. Abstract : As biodiversity is often correlated with ecosystem function, it is important to study biodiversity to conserve ecosystems. To assess the ability to estimate species diversity using spectral diversity, we collected vegetation survey data and ground‐level hyperspectral data from community plots consisting of multiple species. There was a positive correlation in the visible region using band depth, a positive correlation in the near‐infrared region using first derivatives, and weak to no correlation in the red‐edge region using either spectral transformation technique; thus, species diversity can be estimated using spectral diversity, but the correlation depends on the spectral region examined and the spectral transformation technique used.